Estudo da competência de Saccharomy cescerevisiae em co-cultura para a produção de etanol - Santos, Mayara Vieira (2017)
Usually the inoculum used during the beginning of the harvest of ethanol production is constituted by the combination of two or more yeasts strains and in the end the most adapted one will predominate, either inoculated yeast or indigenous wild yeast. The proportion used in these industries are established empirically, of which little is known about the kinetic parameters and the influence that each yeast has on the production of ethanol and on the other metabolites. An experimental design from the blending design with Saccharomyces cerevisiae ATCC7754, S. cerevisiae CAT-1, S. cerevisiae PEDRA-2, S. cerevisiae MONASTRELL strains was proposed to understand how the interaction among the different blends occurs comparing with the ethanol, biomass, acetic acid, glycerol and biomass consumption. This study showed that the inherent characteristics to each yeast can influence the behavior of the kinetics parameters of the culture with two yeasts. It was verified that the combination among three yeasts presented similar metabolic behavior. From the blending design it was possible to elaborate mathematical models that predicts the ethanol, biomass, glycerol, acetic acid and residual sucrose amount in all four yeasts mixtures. It was also possible to identify that the mixture of CAT-1 and PEDRA-2 presented higher ethanol production when cultivated in a 1: 1 ratio, and also in the cultivation with the two yeasts (CAT-1 and PEDRA-2) to CAT-1 was higher in yeast. This research also presents the synthetic cane juice composition and the detail of growth kinetics, substrates consume and production of MONASTRELL yeast products that had not been studied until now.